Neuronal Projections and Putative Interaction of Multimodal Inputs in the Subesophageal Ganglion in the Blowfly, Phormia regina. (9th April 2014) - Maeda, Toru; Tamotsu, Satoshi; Iwasaki, Masayuki; Nisimura, Tomoyosi; Shimohigashi, Miki; Hojo, Masaru K.; Ozaki, Mamiko
Abstract : In flies, the maxillary palp possesses olfactory sensilla housing olfactory receptor neurons (ORNs), which project to the primary olfactory center, the antennal lobes (ALs). The labellum possesses gustatory sensilla housing gustatory receptor neurons (GRNs), which project to the primary gustatory center, the subesophageal ganglion (SOG). Using an anterograde staining method, we investigated the axonal projections of sensory receptor neurons from the maxillary palp and labellum to the SOG or other parts of brain in the blowfly, Phormia regina . We show that maxillary mechanoreceptor neurons and some maxillary ORNs project to the SOG where they establish synapses, whereas other maxillary ORNs terminate in the ipsi- and contralateral ALs. The labellar GRNs project to the SOG, and some of these neural projections partially overlap with ORN terminals from the maxillary palp. Based on these anterograde staining data and 3D models of the observed axonal projections, we suggest that interactions occur between GRNs from the labellum and ORNs from the maxillary palp. These observations strongly suggest that olfactory information from the maxillary palp directly interacts with the processing of gustatory information within the SOG of flies.